The Concept of Harmony and Modulation in Kwanji Sempidi's Gambang - Mariyana, I Nyoman (Institut Seni Indonesia Denpasar, 2023)
Gamelan Gambang is a Balinese musical ensemble that has a unique and distinctive characteristic of its musicality. Gamelan Gambang belongs to gamelan saih pitu (seven notes), where in one octave the tone consists of seven principal notes. Each of the instruments in the Gambang Kwanji Sempidi gamelan has a different concept of tone harmonization and tone modulation. The method used in this study uses a type of qualitative descriptive research method through data collection using observation, interview, discography, and documentation methods. While measuring the frequency of the tone using the Curltone application tool. Through this method, in the Gambang Kwanji Sempidi gamelan, harmony appears in the arrangement of the Gambang tones on each Gambang instrument. Harmony is related to the interval or pitch distance. The pitch distance between dAng (A) and dang (a) is called ngembat or octave, the distance between dAng (A) and dEng (e) is called ngepat or ngempyung (kwint), while the distance between dAng (A) and dOng (o) tones called nelu or quart. If they are hit together in one tone simultaneously, four forms of tone harmonization patterns occur (nelu, ngepat, and ngembat). The harmony playing pattern on the xylophone is supported by the gambang beater (panggul) which has been set in such a way. The xylophone panggul has a different distance between the right and left pairs of mallets. The left pair spans four notes, while the right pair spans five notes. The Gambang Kwanji modulation system, namely the transition from one basic tone to another, is called Sengkeran. In the game, there is a change of one note in the order of the notes used. This sengkeran is found in the Gambang Labdha and Manukaba songs.